Management and impact of obesity in Canada: A real-world survey of people with obesity and their physicians - Jennifer Glass; Sophie Carter; Esther Artime; Victoria Higgins; Lewis Harrison; Andrea Leith; David CW. Lau; Ian Patton; Jennifer L. Kuk (Obesity Pillars)
Background: Obesity is a chronic relapsing disease associated with multiple complications. This study described real-world demographic/clinical characteristics, including obesity-related complications (ORCs), prescribing rationale, and patient-reported outcome measures (PROMs) for adults living with obesity in Canada accessing treatment. Methods: This was a cross-sectional survey of physicians and consulting people with obesity (PwO) in Canada with retrospective data capture in a real-world setting. Canadian data were drawn between July and November 2022 from the multinational Adelphi Real World Obesity Disease Specific Programme™. Consulting PwO were required to be on a weight management program and/or have a current body mass index of ≥30 kg/m2. Physicians completed questionnaires for the next 3–5 consecutive PwO seen in their routine clinical practice. A quota was applied for obesity management medication (OMM). PROMs including Work Productivity and Activity Impairment (WPAI) questionnaire were provided voluntarily by PwO. Analyses were descriptive. Results: Overall, 50 physicians (35 general practitioners, 15 endocrinologists) and 199 PwO were analyzed. More than 85 % of PwO had ≥1 ORC. The most common ORCs were hypertension, dyslipidemia, depression, and type 2 diabetes, and one-quarter to one-half of ORCs were not optimally controlled. Approximately two-thirds of the cohort were employed full-time, almost half had private insurance, and almost 70 % were classified as high socio-economic status. Mean number of weight-reduction attempts over the past 3 years was 2.9. Pharmacological treatment for obesity was common among those with ORCs. A general trend towards greater work impairment among people with ORCs than for PwO without ORCs was observed. Conclusions: Among PwO participating in our study, ORCs were common, often uncontrolled, and their presence impacted the likelihood of obesity treatment and possibly impaired work productivity. Medical treatment for obesity was often delayed until ORCs developed, suggesting that preventative healthcare measures are not the norm for PwO in Canada. A large proportion of PwO had high socioeconomic status, suggesting that PwO who access treatment may not be representative of the overall population of PwO in Canada.